Analisis Pengaruh Gig Economy Dan Mindfulness Terhadap Loyalitas Pekerja Melalui Mediasi Kesejahteraan - Ardiatama, Fadhilah Rafi; Irmawati, Irmawati (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the influence of gig economy and mindfulness on worker loyalty through welfare mediation. The increasingly widespread gig economy phenomenon and awareness of the importance of welfare encouraged this research. This study uses a quantitative method with a descriptive approach. The population in this study is workers involved in the gig economy sector in Solo Raya. The sample was taken by purposive sampling of 80 respondents through google form. The data was analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study show that the gig economy has a negative effect on worker loyalty, and does not directly affect welfare. Mindfulness has a positive effect on the welfare and loyalty of workers. Well-being has been shown to mediate the relationship between mindfulness and worker loyalty. However, welfare has not been proven to mediate the relationship between the gig economy and worker loyalty.